On-Line Preconcentration and Simultaneous Determination of Cu and Mn in Water Samples Using a Minicolumn Packed with Sisal Fiber by MIP OES - Javier Silva; Mariela Pistón (Molecules, 2021)
An on-line preconcentration system for the simultaneous determination of Copper (Cu) and manganese (Mn) in water samples was developed and coupled to a microwave-induced plasma optical emission spectrometer (MIP OES). The flow injection system was designed with a minicolumn packed with sisal fiber (Agave sisalana). A multivariate experimental design was performed to evaluate the influence of pH, preconcentration time, and eluent concentration. Optimal conditions for sample preparation were pH 5.5, preconcentration time was 90 s, and HCl 0.5 mol L−1 was the eluent. The main figures of merit were detection limits 3.7 and 9.0 µg L−1 for Cu and Mn, respectively. Precision was expressed as a relative standard deviation better than 10%. Accuracy was evaluated via spiked recovery assays with recoveries between 75–125%. The enrichment factor was 30 for both analytes. These results were adequate for water samples analysis for monitoring purposes. The preconcentration system was coupled and synchronized with the MIP OES nebulizer to allow simultaneous determination of Cu and Mn as a novel sample introduction strategy. The sampling rate was 20 samples/h. Sisal fiber resulted an economical biosorbent for trace element preconcentration without extra derivatization steps and with an awfully time of use without replacement complying with the principles of green analytical methods.